A Journey into the World of Targeted Therapy: A Review of Gene Therapy, Stem Cell Therapy, and Cell Reprogramming in Cardiovascular Medicine - Forough, Reza; Gormley, Christine; Scarcello, Catherine; Cube, Stacey; Mattsson, Erney (Recent Patents on Regenerative Medicine, 2012)
Finding a cure for every single disease has been the ultimate dream of mankind throughout history. To this end, generation after generation has witnessed innumerable attempts to rewrite and revise the “book of cures.” Despite the unfinished journey to find treatment for all known diseases, several universal agreements with regard to what constitute the most likely successful strategies have been reached. First, to develop a successful healing outcome, one needs to specifically target the agent(s) causing the disease. Second, the body needs to be freed of the source(s) of the disease. Third, the damaged body parts/tissues need to be replaced with healthy ones. In the framework outlined above, three disciplines in the field of biomedical science, namely, gene therapy, stem cell therapy, and cell reprogramming, appear as the leading strategies to fulfill these goals, as they possess all the desired elements for treating disease. This patents review describes the past and present status of these three disciplines with an emphasis on advances in the cardiovascular field for each discipline.
Keywords: Intramyocardial injection